Impacts of ocean acidification on carboxylated carbon nanotubes effects induced in the clam species Ruditapes philippinarum - De Marchi, Lucia (2020)
Although the increased production of nanoparticles (NPs) has raised extensive concerns about the potential toxic effects on aquatic organisms, as well as the increasing evidences which documented the impact of ocean acidification (OA) on the physiology and fitness of marine invertebrates, limited number of studies reported their combined toxic effects. For these reasons, in the present study, we investigated the physiological and biochemical responses of one of the most economically important bivalve species in the World, the Manila clam Ruditapes philippinarum, after the exposure to an environmnetally relevant concentration of carboxylated carbon nanotubes and predicted OA conditions. The results showed that the organisms were not only susceptible to NPs but also to seawater acidification. Different responses between low pH and NPs for most tested biomarkers were observed, both in terms of physiological (respiration rate) and biochemical responses (metabolic capacity, oxitative status and neurotoxicity). Acidified pH significantly decreased the respiration rate and metabolism and increased the energy reserves consumption. Moreover, increase of the oxidative damage was also detected under this condition confirming that the mechanism of enhanced toxicity in the organisms should be attributed to lower aggregation state with more suspended NPs in acidified seawater, indicating that seawater acidification significantly influenced the impact of the used NPs in the exposed organisms.